The Quality of Health Care Services at The Alalak Selatan Community Health Center Banjarmasin City - Erna Suriyani; Deyanti; Yuliana Putri; Hedya Ivana Silam; Ika Nazwa Putri (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to determine the quality of health services at the Alalak Selatan Community Health Center in Banjarmasin City. This study employs a descriptive research design and a qualitative approach. Data collection was conducted through observation, interviews, and documentation. The findings of the study indicate that the quality of service at the Alalak Selatan Community Health Center, as measured by the timeliness of service—specifically regarding waiting times and processes—is not yet optimal and has not been able to fully meet the established completion targets. In terms of politeness and friendliness in providing service, the quality is quite good; however, friendliness tends to decrease when there are large numbers of patients in line. In terms of service accuracy, the quality is already good. The quality of public service, as measured by the ease of accessing services, is quite good, and the comfort level in receiving services is also quite good, although improvements are still needed. Therefore, it is necessary to optimize the use of the online queueing application with clear service time estimates. Direct outreach to the public regarding the use of the online queueing application should be conducted so that all patients can register through the application. Comfort in the patient waiting area should be improved, and additional computers should be provided to facilitate the service process.